I luv u baby - DJ Pippi; DJ WT; MCA Music; WT Records ([New York] : MCA Music Publishing, 1994)
Contains eight different mixes of the single.
CD 1 : Radio version (3.34) -- Dancing Divaz radio mix (3.52) -- No swing mix (7.18) -- Dancing Divaz club mix (6.44) -- Tall Paul mix (6.51) -- Yosh <lovedeejay Akemi> mix (5.29 )-- Roc & Kato vs. W.T. & Pippi (7.44) -- Dancing Divaz rhythm mix (5.23)
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English; Dance music